Energy and nutrient recovery by treating wastewater with fluidised-beds of immobilised algae. (December 2020) - Kube, Matthew; Mohseni, Arash; Fan, Linhua; Roddick, Felicity
Graphical abstract: Highlights: Fluidised-beds of immobilised S. abundans and C. vulgaris treat secondary effluent. Algae grew contained within beads, assimilating N and P to achieve low concentrations. Methane generated by digestion of the algal biomass quantified and modelled. Reactor demonstrated to be suitable for integration into wastewater treatment plants. Abstract: Beads of alginate-immobilised algae can be used to remove nutrients from wastewater in a compact reactor and to facilitate algal biomass collection for resource recovery. Fluidised-bed reactors containing entrapped Chlorella vulgaris or Scenedesmus abundans were fed secondary effluent containing TP (8.9 ± 0.45 mg/L), TN (18.3 ± 0.7 mg/L), N-NO3 − (5.3 ± 0.4 mg/L) and N-NH4 + (9.4 ± 0.2 mg/L) at 12 h hydraulic retention time. These conditions mimicked reduced aeration of the activated sludge process to decrease energy consumption and fugitive gas emissions. The S. abundans reactor operated for 30 days before biomass harvest and bead regeneration was required, longer than the reactor with C. vulgaris (8 days). S. abundans grew at 3.3 ± 0.6 × 10 6 cells/mL/d, and removed TP to 0.90 ± 0.26 mg/L and TN to 9.8 ± 1.1 mg/L on average; it completely removed NH4 +, but did not remove N-NO3 − . This demonstrated that the algal system could be used to treat the effluent to <1 mg/L TP/L and <10 mg TN/L. Co-digestion of S. abundans biomass, with and without enzymatic pre-treatment, with wastewater sludge showed that the untreated biomass generated more biomethane (248 ± 10 mL CH4 /g VS) than the pre-treated biomass (178 ± 13 mL CH4 /g VS). This indicated that the algal biomass could be directly added to an existing anaerobic digestion process to improve biomethane production and subsequent energy recovery, and the digestate used as fertiliser. Integration of the immobilised algae system into wastewater treatment trains is discussed based on these results.